The Effect of Moon Phases on Gill Net Fishing Results in Penampi and Kelebuk Villages of Bengkalis Regency - Sofian, Alifa Khansa; Nofrizal, Nofrizal; Jhonnerie, Romie; Fatmawati, Riska (Journal of Coastal and Ocean Sciences, 2025)
This study aims to examine the differences in gill net catch results with the lunar phase in Penampi Village and Kelebuk Village, Bengkalis Regency. Data were collected from January 5 to April 5, 2024, involving 15 fishermen (eight from Penampi Village and seven from Kelebuk Village). Global Positioning System (GPS) technology was used to record the route of the boats, the number of catches (tails), and the total weight (kg) during fishing activities. Statistical analysis using an independent t-test was conducted to evaluate the effect of the lunar phase on catch results. The study found that the lunar phase did not significantly affect the number of catches (fish). However, catch weight was significantly influenced by the dark lunar phase (173.9 kg) and the semi-dark phase (30.5 kg). This study provides important insights into gill net fishing practices in the region. Fishermen are advised to focus on fishing during the dark moon phase, as this period yields the highest catch weight. During the semi-dark phase, fishermen are advised to consider alternative strategies, such as adjusting fishing locations and times to improve catch outcomes. Additionally, weather and sea conditions should be monitored to support the success of fishing activities.